Khidā’ al-Mutaṭarrifīn fī Istikhdām al-Lugah al-‘Arabiyyah Wasīilah li al-Taṭarruf - Sulaiman, Raziyu Lawal; Tofa, Umar Uba; Shehu, Idris (Study Program of Arabic Language Teaching, 2023)
This research attempts to explain and clarify the relationship between Boko Haram and the Arabic language and its use of Arabic, especially under a religious slogan, and that this relationship is arbitrary, neither a religious nor an Arabic linguistic relationship. It also addresses the discovery of Boko Haram as a terrorist sect financed by a terrorist group in a hidden guise to achieve an aim they seek. The research includes three axes after the introduction. The first axis is limited to introducing Boko Haram, the second axis talks about Boko Haram and its use of the Arabic language under a religious slogan, the third axis is the negative effects left by the Boko Haram group, and then the conclusion, which mentions the findings and results of the research.